The Quantum-Classical Transition as an Information Flow - Kowalski, Andres Mauricio (2010)
We investigate the classical limit of the semiclassical evolution with reference to a well-known model that represents the interaction between matter and a given field. This is done by recourse to a special statistical quantifier called the "symbolic transfer entropy". We encounter that the quantum-classical transition gets thereby described as the sign-reversal of the dominating direction of the information flow between classical and quantal variables.